Tingkat Kepuasan Pasien Dalam Penyelenggaraan Pelayanan Kesehatan Lingkungan Pada Rumah Sakit Islam Berdasarkan Standar Pelayanan Minimal Mutu Syariah - Sumantri, Arif; Fajrini, Fini; Andriyani, Andriyani; Lusida, Nurmalia; Dzikriyati, Nadiva (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Good quality health care is seen as the patient's right and is the responsibility of hospital personnel (Zineldin, 2006). The quality of service created by agencies or hospitals aims not only to increase patient satisfaction, but also to improve hospital standards and employee performance as well. Of course, it is not only oriented towards material commitment but is also carried out through practice as part of the value of worship (Yunus, 2012). To determine the relationship between the implementation of Islamic Health Services at RSI Cempaka Putih and Patient Satisfaction. This study is a quantitative research with a cross sectional method. Respondents filled out a questionnaire which was circulated through the inpatient manager which was then forwarded to the inpatient room, especially the post-surgical patient room. The data obtained was tested using the Spearman statistical test to see the correlation between variables and patient satisfaction. The sample of post-surgical inpatients consisted of 88 respondents. It was found that 54% of patients had high expectations for Islamic services. However, in reality, the majority of satisfaction figures for Islamic services are rated as quite satisfied, 73% and 25% satisfied. The results of the Spearman correlation test show that the implementation of sharia mandatory quality services at RSI Cempaka Putih on the satisfaction of post-surgical inpatients has a weak relationship but is not statistically significant. However, based on the results of the analysis of each question, a significant relationship was found between patient satisfaction and mandatory quality services, namely for the variable wearing a hijab for breastfeeding mothers. Meanwhile, in general, the implementation of minimum sharia services has an insignificant relationship with the satisfaction of post-surgical inpatients at RSI Cempaka Putih. Respondent satisfaction figures cannot be separated from the hospital's commitment to implementing Islamic services according to standards. The consistency of the implementation of Islamic services can be seen from how Islamic concepts are included in planning and actualization, there are verbal and written policies implemented by the hospital. Sharia/Islamic concepts must be present in the planning, both in the strategic plan (strategic plan) which is not limited to a vision and mission but is also actualized in 4 things, namely: balanced human resources, adequate budget, infrastructure mechanisms and clear authority. As a hospital that applies Syaria standard, it is also necessary to pay attention to aspects of environmental cleanliness and health.